FLAIR Vascular Hyperintensity Preceding Stroke in Cryptococcal Meningitis - Sanossian, Nerses (2011)
BACKGROUND AND PURPOSE: Ischemic stroke is a common complication of cryptococcal meningitis. Fluid attenuated inversion recovery vascular hyperintensity (FVH) is a neuroimaging marker of sluggish blood flow usually seen in the setting of acute stroke. FVH have never been described in the setting of meningitis. METHODS: Case report. RESULTS: A 20-year-old man with cryptococcal meningitis and a magnetic resonance imaging demonstrating FVH had subsequent neurological deterioration and was found to have bilateral ischemic stroke. CONCLUSIONS: In conditions with high risk of stroke, such as meningitis, the presence of FVH should alert the clinician to the possibility of impending infarction.